Pharmacological interventions for chronic pain in children: an overview of systematic reviews. Issue 8 (August 2019) - Eccleston, Christopher; Fisher, Emma; Cooper, Tess E.; Grégoire, Marie-Claude; Heathcote, Lauren C.; Krane, Elliot; Lord, Susan M.; Sethna, Navil F.; Anderson, Anna-Karenia; Anderson, Brian; Clinch, Jacqueline; Gray, Andrew L.; et al.
Abstract : Abstract: We know little about the safety or efficacy of pharmacological medicines for children and adolescents with chronic pain, despite their common use. Our aim was to conduct an overview review of systematic reviews of pharmacological interventions that purport to reduce pain in children with chronic noncancer pain (CNCP) or chronic cancer-related pain (CCRP). We searched the Cochrane Database of Systematic Reviews, Medline, EMBASE, and DARE for systematic reviews from inception to March 2018. We conducted reference and citation searches of included reviews. We included children (0-18 years of age) with CNCP or CCRP. We extracted the review characteristics and primary outcomes of ≥30% participant-reported pain relief and patient global impression of change. We sifted 704 abstracts and included 23 systematic reviews investigating children with CNCP or CCRP. Seven of those 23 reviews included 6 trials that involved children with CNCP. There were no randomised controlled trials in reviews relating to reducing pain in CCRP. We were unable to combine data in a meta-analysis. Overall, the quality of evidence was very low, and we have very little confidence in the effect estimates. The state of evidence of randomized controlled trials in this field is poor; we have no evidence from randomised controlled trials for pharmacological interventions in children with cancer-related pain, yet cannot deny individual children access to potential pain relief. Prospero ID: CRD42018086900. Abstract : Supplemental Digital Content is Available in the Text.